Cultural identity and global process - Friedman, Jonathan (Theory, culture & society (Unnumbered), 1994)
Examining ideas ranging from world systems theory to postmodernism, Jonathan Friedman investigates the relations between the global and the local, to show how cultural fragmentation and modernist homogenization are equally constitutive trends of global reality.